Factors that Influence Profitability in the Industrial and Chemical Companies Listed on Indonesia Stock Exchange - Enda Noviyanti Simorangkir; Tony Tony; Jessica Noviyanti; Hartono Hartono; Peter Limas; Fanny Citra (Politeknik Negeri Bali, 2019)
This study aims to determine whether Firm Size, Debt To Equity Ratio, and Working Capital Turnover Ratio partially or simultaneously have a significant effect on profitability in the basic industrial and chemical sector companies listed on the Indonesia Stock Exchange. The theories used in this study are financial management theories and accounting theories related to Firm Size, Debt To Equity Ratio, Working Capital Turnover Ratio and Profitability. The method used in this study is a quantitative approach, a type of descriptive research, the nature of explanatory research, with documentation data collection techniques, the type of data used is secondary data, the sample collection technique uses purposive sampling method. Data analysis used is multiple linear regression. The population used was 69 companies and a sample of 27 samples (108 samples in 4 years). The classic assumption test used is the normality test, multicollinearity test, autocorrelation test and heteroscedasticity test. The test results of the coefficient of determination show Firm Size, Debt To Equity Ratio, and Working Capital Turnover Ratio to Profitability of 34.5%. The conclusion of this study is Simultaneous Firm Size, Debt To Equity Ratio, and Working Capital Turnover Ratio have an effect on Profitability in the basic industrial and chemical sector companies listed on the Indonesia Stock Exchange in 2014-2017. While partially Firm Size does not affect Profitability. Partially the Debt To Equity Ratio, and the Working Capital Turnover Ratio affect Profitability in the basic and chemical industry companies listed on the Indonesia Stock Exchange